Eksistensi Tari Kabasaran Pada Masyarakat Minahasa - Nismawati, Nismawati; Oruh, Shermina; Agustang, Andi (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This research discusses the existence of Kabasaran dance with the Minahasa culture in Tondano. This research was carried out to find out by exploring the meaning of cultural heritage that needs to be revealed. The diversity of Minahasa culture has a cultural meaning from the ancient Tou Minahasa generation until now which is still clear in its existence in the community and it needs to be translated into the meaning of that culture. One of them is the Kabasaran dance, which is a war dance that has three stages consisting of separate dance forms that have meaning. The research used is qualitative research with ethnographic methods. The informants taken consisted of cultural figures and performers of the Kabasaran dance. Collecting data through observation, interviews and documentation. The analysis conducted for qualitative data refers to the model proposed by Miles and Huberman. Kabasaran dance has dance equipment including accessories, uniforms, swords, and shields. Dance equipment has cultural symbols that need to be translated. These symbols have a meaningful and beneficial life value for generations of cultural heirs. The Kabasaran dance is one of the local wisdom that is preserved and is a regional cultural specialty and is a cultural asset of Indonesia. Kabasaran dance implicitly describes the unity of the Minahasa people in providing a sense of security and defending their homeland with all their strength.